ONLINE TRAVEL COMPANIES AND CONSUMER ENGAGEMENT IN THE ERA OF ARTIFICIAL INTELLIGENCE - et. al., Prachi Vaidya (International Journal of Modern Agriculture, 2021)
Unlike past generations, the digital natives of a modern generation are remodelling the system through which new technologies are dispensed and democratized, to change how the next generation benefits the merits of developing technologies quickly, it offers an inclusive space. AI is disrupting many industries including the travel industry. AI analyses the searching patterns of the consumer and then accurately examines these patterns to forecast consumer requirements. Based on these predictions, AI technology facilitates the travel companies to offer relevant suggestions to its consumers making it accelerated than ever before to organise a trip. Companies are seeking customer engagement with their brands. This paper addresses the Customer engagement process in online travel companies and suggests the use of AI technology to enhance the user experience and further increase customer engagement and retention.